Foreign Business Partners Influence on Technological and Market Knowledge of Company - Starkus, Arūnas (Ekonomika, 2002)
The article is focused on internationalisation process of the new venture. Two cases of Lithuanian companies were analysed in order to understand what influences successful and balanced growth of export. Companies, selected for case analysis are members of Libra group. Both they were founded by the same people. They have had many similarities (industry, size, location, administration, the same zero level of technological and market knowledge at the starting point, etc.) except the results of the first three years of activity. This period of both companies was analysed using historical case analysis methodology. It was established that in case when incremental technological and market learning is coordinated with appropriate export client type, the results of the activity were better. That is why export according to principles of Uppsala internationalisation model could be marshalled to four steps: 1, Sale through middlemen in host country. 2. Export to small middlemen company. 3. Export to big middlemen company. 4. Export to user of the good. The positioning of company on certain step of export implements appropriate possibilities to diminish technological and market uncertainties through learning from trade partners or by help of them.